2013
DOI: 10.1371/journal.ppat.1003660
|View full text |Cite
|
Sign up to set email alerts
|

The DAF-16/FOXO Transcription Factor Functions as a Regulator of Epidermal Innate Immunity

Abstract: The Caenorhabditis elegans DAF-16 transcription factor is critical for diverse biological processes, particularly longevity and stress resistance. Disruption of the DAF-2 signaling cascade promotes DAF-16 activation, and confers resistance to killing by pathogenic bacteria, such as Pseudomonas aeruginosa, Staphylococcus aureus, and Enterococcus faecalis. However, daf-16 mutants exhibit similar sensitivity to these bacteria as wild-type animals, suggesting that DAF-16 is not normally activated by these bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 64 publications
2
54
2
Order By: Relevance
“…Furthermore, previous work showed that the C. elegans Gα q homolog EGL-30 can activate PLCβ homolog EGL-8 for host defense against Pseudomonas aeruginosa or Microbacterium nematophilum infection (Kawli et al, 2010; McMullan et al, 2012). In addition, activation of EGL-30 during fungal infection triggers EGL-8 and Ca 2+ release to activate dual oxidase, or Duox (Zou et al, 2013). With this precedent in mind, we investigated the role of the EGL-30 – EGL-8 axis in HLH-30 activation by infection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, previous work showed that the C. elegans Gα q homolog EGL-30 can activate PLCβ homolog EGL-8 for host defense against Pseudomonas aeruginosa or Microbacterium nematophilum infection (Kawli et al, 2010; McMullan et al, 2012). In addition, activation of EGL-30 during fungal infection triggers EGL-8 and Ca 2+ release to activate dual oxidase, or Duox (Zou et al, 2013). With this precedent in mind, we investigated the role of the EGL-30 – EGL-8 axis in HLH-30 activation by infection.…”
Section: Resultsmentioning
confidence: 99%
“…In such pathway, a GPCR-Gα 12 -PLCγ-PKCδ pathway controls a STAT-type transcription factor (Dierking et al, 2011; Ziegler et al, 2009; Zugasti et al, 2014). C. elegans Gα q also has known roles upstream of PLCβ for the regulation of host defense against P. aeruginosa and oxidative stress (Kawli et al, 2010) and for the upregulation of transcription factor DAF-16 in the epidermis during D. coniospora infection (Zou et al, 2013). Furthermore, C. elegans Gα q was recently shown to control both innate immunity and infection avoidance behavior against M. nematophilum (McMullan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, A. aegypti ILP3 ( Aa ILP3) has been shown to bind to the insulin receptor, while Aa ILP4 binds to an uncharacterized mosquito membrane protein (Wen et al, 2010), suggesting that As ILPs could signal through multiple receptors to regulate anti-parasite effector genes. Alternatively, As ILP-specific activation of IIS pathway proteins, most notably FOXO, ERK and glycogen synthase kinase 3 (GSK3) could facilitate diverse direct effects on effector gene transcription as well as modulation of NF-κB-dependent signaling (Becker et al, 2010; Pakpour et al, 2012; Zou et al, 2013; Surachetpong et al, 2009; Martin et al, 2005). Hence, further study of As ILPs and mechanisms whereby As ILPs signal host mosquito cells are likely to provide novel insights into parasite manipulation of mosquito defenses against infection.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, virulence factor-mediated increases in IIS during Pseudomonas aeruginosa infection in C. elegans suppressed anti-microbial peptide (AMP) gene expression, increasing bacterial colonization (Evans et al, 2008), while insulin receptor daf-2 mutants were resistant to bacterial pathogens (Garsin et al, 2003). In more recent studies, pathogen resistance in C. elegans was observed to occur independently of the DAF-2 pathway, resulting instead from direct pathogen activation of the IIS downstream target DAF-16, a forkhead box O (FOXO) transcripton factor (Zou et al, 2013). Our own studies affirmed that PI3K/Akt signaling is responsible for human insulin-induced repression of the innate immune responses of A. stephensi to P. falciparum infection (Pakpour et al, 2012), demonstrating that mosquito IIS regulates innate immune responses in a manner similar to that observed in D. melanogaster and C. elegans .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to regulating metabolism, FoxO is also a highly conserved regulator of the immune response in animals including cnidarians, ecydysozoans and mammals (Becker, et al 2010;Bridge, et al 2010). DAF-16, the C. elegans orthologue of FoxO, confers resistance to fungal pathogens and is also activated in response to oxidative stress and epidermal wounding (Zou, et al 2013). FoxO activity also has a more direct effect on the immune response through the regulation of antimicrobial peptide expression, a role that is conserved from the basal metazoan Hydra to more morphologically complex animals such as Drosophila and humans (Becker, et al 2010;Bridge, et al 2010).…”
Section: Choanocytes Have Dual Roles In Immunity and Digestionmentioning
confidence: 99%